STUDI KOMPARATIF PENDAPATAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) PADA USAHA OLEH-OLEH KHAS BENGKULU SEBELUM DAN DI MASA PANDEMI COVID-19 - Mardianti, Rara; Lustiana, Riska; Yarmunida, Miti; Afrida Indra, Yetti (Juremi: Jurnal Riset Ekonomi, 2022)
This study aims to compare the income of MSMES at souvenir shops typical of Bengkulu before and during the Covid 19 pandemic and to find out the survival strategies that can be used by Bengkulu souvenir shops during the Covid-19 pandemic. The method used in this study uses a descriptive quantitative approach. The results showed that there were significant differences in the income level of MSMES in Bengkulu souvenir shops before and during the pandemic. Based on the analysis of the marketing strategy of MSME actors in Bengkulu souvenir shops, the following survival strategies can be used: 1) Increasing Human Resources, 2) Implementing Creative Innovations, 3) E-Marketing Strategies In Promotion, 4) Product And Service Quality Improvement, 5) Production Cost Reduction.